Wave propagation in a network of extended Morris–Lecar neurons with electromagnetic induction and its local kinetics - Rajagopal, K; Moroz, I; Karthikeyan, A; Duraisamy, P (Springer, 2020)
An extended Morris–Lecar neuron model incorporating electromagnetic flux coupling and external excitation is proposed. The complete dynamical behavior of the new model is investigated as autonomous and non-autonomous forms. Multistability and coexisting attractors are shown for the new neuron model. It is shown that when external excitation is introduced, the complete dynamical behavior of the system changes compared to the non-excited version. To study the wave propagation pattern, we construct a network of the extended neuron model and study the generation of spiral waves under various conditions of coupling strength, stimuli parameters and system parameters. We have also studied the wave propagation pattern considering the time-based chaotic-periodic neurons in the network.